The Role of Job Satisfaction to Reduce Nurse Turnover Intention: A Systematic Review - Dewanti, Nisa; Purwanza, Sena Wahyu; Prakosa, Mira Melynda (Fundamental and Management Nursing Journal, 2023)
Introduction: Job satisfaction is a condition in which a person feels positive about the job and its characteristics. The conditions are synonymous with satisfying, happy, and grateful. A person with high job satisfaction tends to stay longer in the organization and supports the organization. The purpose of systematic review aims to search published articles on job satisfaction among nurses. Methods: This study applied a systematic review. Literature was searched in three databases namely PubMed, Science Direct, and Semantic Scholar with keywords "job satisfaction”, "turnover intention”, "intent to stay”, and "nurse”. Search strategies focused on the published article from January 2018 to December 2022. Results: Fifteen (15) articles were analyzed. The finding revealed job satisfaction significantly reduced turnover intention in nurses. The role of job satisfaction in reducing turnover intention at nurses can be done directly or as a mediating factor. Job satisfaction has a fully mediating role in reducing turnover intention in nurses. Job security, self-seeking, unappreciativeness, negative state of mind, relational coordination, workload, burnout, and work environment are variables that mediated job satisfaction. Meanwhile, job burnout, job organizational, affective and normative commitment have a role as a mediator between job satisfaction and turnover intention in nurses. Conclusions: The current findings underline the urgency of establishing and maintaining supportive and conducive working environment. Nursing management in the clinical setting has a responsibility to create a sustain work setting that in line with the organization goals and professional development.